Online / offline activisms: Las redes sociodigitales y los grupos políticos afroreligiosos en el conurbano bonaerense - Abalos Irazabal, Mariana (Instituto de Altos Estudios Sociales, 2021)
An aspect that characterizes our society today is the increasing presence of different digital technologies in the daily lives of the people. In particular, there is a growing use of socio-digital networks (mainly Facebook and WhatsApp) as means of communication par excellence in diverse orders of life: peer groups, institutional relations (work, educational, recreational), among others. Far from being merely useful accessory for communication, socio-digital networks are consolidating as relevant spaces for socialization: the interactions that are interwoven online, many times, directly influence those that occur offline by which reality is experienced by the users. actors, and vice versa. This takes place in all areas, both in those already mentioned (work spaces, education, family, friends), and - in this article - in areas of religious practices. In this paper, I will reflect on how this mutual permeability occurs between online and offline interactions experienced by Afro-religious political groups in Buenos Aires and what are the main characteristics that define them.